Impact of Roadside Dust on Growth, Development andCellular Characteristics of Tomato Plants - Raihan, Md. Ashik; Abdul Mannan, Muhammad; Choity, Mst. Afsana Yasmin; Samad, Md. Abdus; Ali, Md. Raihan; Rahman, Md. Mahfuzur; Tasnim, Mahrupa; Biswas, Md. Mahirul Islam (International Journal of Scientific Research and Management (IJSRM), 2024)
This thesis investigates the effect of roadside dust on the growth and development of tomato plants, specifically focusing on plant height, leaf number, terminal leaf area, lateral leaf area, root fresh weight, root dry weight, shoot fresh weight, shoot dry weight, and cellular characteristics. The study examines seven treatment groups representing varying concentrations of roadside dust applied to the plants. The results reveal significant variations in the measured parameters, indicating that the treatments had a significant effect on most of the parameters, except for root dry weight. The plant height, terminal leaf area, leaf number, and lateral leaf area showed a decreasing trend with increasing dust concentration, suggesting hindrance in vertical growth and leaf development. Root fresh weight, shoot fresh weight, and shoot dry weight also exhibited a decreasing trend as the concentration of dust increased, indicating a negative impact on root and shoot biomass. The cellular characteristics, such as guard cell, subsidiary cell, and epidermal cell measurements, demonstrated a decrease in values as dust concentrations increased, indicating adverse effects on cellular growth and development. Overall, the findings indicate that roadside dust has a detrimental effect on the growth and development of tomato plants, including biomass accumulation, leaf expansion, and cellular characteristics. Mitigation strategies, such as regular leaf cleaning, proper irrigation, and air pollution control, are recommended to minimize the negative impacts of roadside dust on plant growth and ensure optimal crop production and environmental sustainability.